Chronic Intra-Uterine Ureaplasma parvum Infection Induces Injury of the Enteric Nervous System in Ovine Fetuses - Heymans, Cathelijne; de Lange, Ilse H.; Hütten, Matthias C.; Lenaerts, Kaatje; de Ruijter, Nadine J. E.; Kessels, Lilian C. G. A.; Rademakers, Glenn; Melotte, Veerle; Boesmans, Werend; Saito, Masatoshi; Usuda, Haruo; Stock, Sarah J.; et al. (Frontiers in Immunology, 2020)
Background: Chorioamnionitis, inflammation of the fetal membranes during pregnancy, is often caused by intra-amniotic (IA) infection with single or multiple microbes. Chorioamnionitis can be either acute or chronic, and is associated with adverse postnatal outcomes of the intestine, including necrotizing enterocolitis (NEC). Neonates with NEC have structural and functional damage to the intestinal mucosa and the enteric nervous system (ENS), with loss of enteric neurons and glial cells. Yet, the impact of acute, chronic or repetitive antenatal inflammatory stimuli on the development of the intestinal mucosa and ENS has not been studied. The aim of this study is therefore to investigate the effect of acute, chronic and repetitive microbial exposure on the intestinal mucosa and ENS in premature lambs. Materials and Methods: A sheep model of pregnancy was used in which the ileal mucosa and ENS were assessed following IA exposure to lipopolysaccharide (LPS) for 2 or 7 days (acute), Ureaplasma parvum (UP) for 42 days (chronic) or repetitive microbial exposure (42 days UP with 2 or 7 days LPS). Results: IA LPS exposure for 7 days or IA UP exposure for 42 days caused intestinal injury and inflammation in the mucosal and submucosal layer of the gut. Repetitive microbial exposure did not alter injury of the terminal ileum. Chronic IA UP exposure caused significant structural ENS alterations characterized by loss of enteric neurons and glial cells whereas no ENS changes were found when these chronic UP-exposed fetuses were re-exposed to LPS for 2 or 7 days. Conclusion: The in utero loss of enteric neurons and glial cells following chronic UP exposure corresponds with intestinal changes in neonates with NEC, and may therefore form a novel mechanistic explanation for the association of chorioamnionitis and NEC.